ANALISIS KONSEP BRANDING PRODUK KOSMETIK HALAL DI MEDIA SOSIAL PERSPEKTIF ROGERS THEORY ON DIFFUSION OF INNOVATION - Naela Maghfiroh (AT-TAWASUL, 2025)
This study aims to explain that the Government through BPJPH MUI has initiated an idea in the form of innovation in implementing halal certificates for all consumer products and uses, especially cosmetics. This innovation is one of the government's ways to maintain the safety of a product so that it is guaranteed halal and free from harmful substances. The purpose of this study is to see how the diffusion of halal certificate innovation in society. The research method used is descriptive qualitative. In this study, the researcher used the Diffusion of Innovation Theory by Everett M. Rogers and Floyd Shoemaker by analyzing 4 main indicators, namely innovation; time period; members of the social system and communication channels. The results of this study, the application of halal cosmetic product branding using this theory as a whole has met the diffusion indicators. In addition, the stages offered by this diffusion theory also help in branding halal cosmetics on social media, namely the stages of knowledge, persuasion, decision, implementation and conformation.